PENGARUH PERMAINAN BUBUR KERTAS BERTEKSTUR TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA DI TAMAN KANAK-KANAK SYUKRA CENDEKIA MADANI - Sara Mawaddah; Setiyo Utoyo; Farida Mayar; Indra Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of textured paper pulp play on improving children's fine motor skills, as well as to contribute to the development of more effective and enjoyable methods of fine motor stimulation for early childhood. The background of this study is that the fine motor skills of children have not developed well, with some children still unable to hold a pencil properly. When using scissors, they also struggle to open and close the scissors with one hand. This study employs a quantitative approach using an experimental method designed as a quasi-experiment. The study population included all children at Syukra Cendekia Madani Kindergarten, while the sample was taken from classes B1 and B2, each with 10 children. Data collection was conducted through tests and analyzed using normality tests, homogeneity tests, and hypothesis tests. The research findings show that in the experimental class, the average pre-test score was 17.7, which increased to 23.1 on the post-test. The sig. (2-tailed) value obtained from the independent sample t-test showed a significant value of 0.006 < 0.05, indicating a significant difference between the two groups. This means that textured paper porridge games have an effect because they are able to provide rich manipulative stimuli and stimulate children's fine motor skills through activities such as squeezing, printing, and shaping